Epitaxial strain-engineered self-assembly of magnetic nanostructures in FeRh thin films. (5th December 2016) - Witte, Ralf; Kruk, Robert; Molinari, Alan; Wang, Di; Schlabach, Sabine; Brand, Richard A; Provenzano, Virgil; Hahn, Horst
Abstract: In this paper we introduce an innovative bottom–up approach for engineering self-assembled magnetic nanostructures using epitaxial strain-induced twinning and phase separation. X-ray diffraction, 57 Fe Mössbauer spectroscopy, scanning tunneling microscopy, and transmission electron microscopy show that epitaxial films of a near-equiatomic FeRh alloy respond to the applied epitaxial strain by laterally splitting into two structural phases on the nanometer length scale. Most importantly, these two structural phases differ with respect to their magnetic properties, one being paramagnetic and the other ferromagnetic, thus leading to the formation of a patterned magnetic nanostructure. It is argued that the phase separation directly results from the different strain-dependence of the total energy of the two competing phases. This straightforward relation directly enables further tailoring and optimization of the nanostructures' properties.